Collaborative Writing in EFL Classroom: Comparison on Group, Pair, and Individual Writing Activities in Argumentative Tasks - Moonma, Jitlada; Kaweera, Chittima (Asian Journal of Education and Training, 2021)
This study focused on comparing the effects on 32 students’ argumentative writing qualities when they worked alone or collaborated in pairs and groups and explored the students’ opinions towards critical thinking across different writing activities. The 32 students were divided into groups of four (n=8), pairs (n=16) and individuals (n=32). Their papers were rated in terms of content, language use, and organization by three raters. The research employed argumentative writing rubrics, semi-structured interview, and observation. From the total of 15 points, the novice learners gained the highest scores when writing in groups (X ̅ = 11.22), followed by pairs (X ̅ = 10.19) and individuals (X ̅ = 8.98). The intermediate learners also gained the highest scores in group work (X ̅ = 11.50), followed by pairs (X ̅ = 10.32), and individual work (X ̅ = 9.04), respectively. Similar to the advanced level, they had the highest scores when working in groups (X ̅ = 11.95), followed by pairs (X ̅ = 10.45), and individuals (X ̅ = 9.45). The findings indicated that group work led to the highest scores in all proficiency levels and in groups, the students’ critical thinking improved regarding analyzing, evaluating and creating information when they brainstormed, shared and discussed all information. In pairs, the students also demonstrated that their critical thinking developed but only in analyzing from sharing information with a partner. In individuals, all proficiency levels reported that critical thinking was not developed as no interaction with peers.